2007
DOI: 10.1016/j.jaci.2007.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Asthma cases attributable to atopy: Results from the Third National Health and Nutrition Examination Survey

Abstract: Background-The percentage of asthma cases attributable to atopy is the subject of debate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
143
3
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(165 citation statements)
references
References 19 publications
8
143
3
7
Order By: Relevance
“…It has been estimated that more than half of asthma cases in the USA can be attributed to allergic sensitisation [36]. Numerous studies have found associations between exposure to indoor allergens and respiratory health, especially in the case of HDM [37,38].…”
Section: Biological Pollutantsmentioning
confidence: 99%
“…It has been estimated that more than half of asthma cases in the USA can be attributed to allergic sensitisation [36]. Numerous studies have found associations between exposure to indoor allergens and respiratory health, especially in the case of HDM [37,38].…”
Section: Biological Pollutantsmentioning
confidence: 99%
“…Risk factors in relationship to asthma have been evaluated in the context of disease inception [e.g., viral infections(1,2,39); environmental exposures (e.g., aeroallergens (40), pollution (41)(42)(43), tobacco smoke (44)(45)(46)(47)) and lifestyle (e.g., living on a farm (48), diet (49), antibiotic use(50)); comorbid conditions (e.g., atopic dermatitis(51), obesity(52)); occupational exposures(3); among others], as well as disease severity (as defined by the risk domaindiscussed subsequently) [hospitalizations (53,54); frequency and severity of exacerbations (55); and loss of lung function (8,56)]. Genetic factors also contribute significantly to disease expression and severity.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Chronic low-level exposure to indoor allergens, and dust mite and cockroach, in particular, may play a major role in both asthma inception and subsequent provocation of symptoms. (61) Although a wide variety of inhaled allergens can provoke asthma symptoms, sensitization to house dust mite(62), cockroach (63), Alternaria (64) and, possibly, cat (40) are important in the pathogenesis of asthma. Dog, but not cat, ownership during infancy has been shown to reduce the subsequent development of allergic sensitization and atopic dermatitis(65); numbers of pets, not the type of furred pet, may also reduce future risk.…”
Section: Exacerbating Factorsmentioning
confidence: 99%
“…The majority of schoolchildren with asthma are allergic to airborne allergens and allergy is a common trigger of asthma symptoms [Arbes et al 2007;Covar et al 2010]. Nevertheless, subcutaneous immunotherapy (SCIT) is still questioned as a safe and efficacious way of treating allergic asthma in children.…”
Section: Introductionmentioning
confidence: 99%